Long-term biomechanical analysis of donor site morbidity after radial forearm free flap. Issue 9 (November 2015) - Riecke, Björn; Kohlmeier, Carsten; Kreiker, Henri; Suling, Anna; Assaf, Alexandre Thomas; Wikner, Johannes; Hanken, Henning; Heiland, Max; Gröbe, Alexander; Rendenbach, Carsten
Abstract: Background: Although the radial forearm free flap (RFF) is a commonly used microvascular graft for head and neck reconstruction, long-term biomechanical results regarding donor site morbidity are rare. Patients and methods: In a prospective panel study, 32 patients were included. Biomechanical assessment was performed preoperatively, three months postoperatively and two years postoperatively. The primary endpoint of the study was grip strength. In addition, the Mayo wrist score, DASH score (disabilities of the arm, shoulder and hand score), fine motor skill strengths (tip pinch, key pinch, palmar pinch) and the range of motion were analysed. Primary defects were closed with local full-thickness skin grafts (FTSG) from the donor site forearm avoiding a secondary defect site. Results: In the long-term analysis, grip strength was reduced in both arms. A significant improvement over time was found only for the donor arm. A persistent deficit of tip pinch strength and dorsal extension was recorded. Persistent sensory limitations occurred in four cases. Patient contentment after two years of follow-up was high and daily life routine was not restricted. Conclusion: Gross and fine motor skill limitations are reversible short-term effects after RFF harvesting and do not restrict daily routine in the long term. These findings substantiate the value of the RFF as a workhorse in reconstructive surgery.